Application Green Accounting in Islamic Perspective and its Impact on Company's Financial Performance - Sukma Uli Nuha; Retno Cahyaningati; Ria Meilan (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2023)
The purpose of this study seeks to describe the applicationgreen accounting. The research method used is a qualitative method with a case study approach. The researchers traced the applicationgreen accounting in companies engaged in animal husbandry in Lamongan Regency. The results of the study show that by disclosing environmental costs, the company will later demonstrate the business ethics it carries out. Not only that, the company will also show how responsible they are in managing existing resources.Green accounting disclosed have a positive impact on the financial performance of a company. The theoretical contribution to this research is to contribute to strengthening the theorycost. The practical contribution of this research can be used as a basis for applying and reporting financial conceptsgreen accounting at the company. This study has described a picture of implementationgreen accounting which is combined with sharia concepts so as to be able to assist company leaders in assessing the company's financial performance.